The role of museum of biological collections in environmental research: a short note - Yap, Chee Kong; Go, Rusea; Bujang, Japar Sidik; Wan Mohd Syazwan; Wahid, Noor Azrizal; Azmai, Mohammad Noor Amal; Annavi, Geetha; Nulit, Rosimah; Ibrahim, Mohd Hafiz; Omar, Hishamuddin; Mustafa, Muskhazli; Abd Aziz, Nor Azwady (MedCrave Group, 2022)
This paper summarizes the use of museum of biological collection (MBC) in comparison of chemical contaminants between the past and the present specimens. It is inferred that MBC provides a unique and crucial insight into the spatio-temporal trend of environmental contamination by establishing a historical reference point.